Palmitoylethanolamide Modulates Inflammation-Associated Vascular Endothelial Growth Factor (VEGF) Signaling via the Akt/mTOR Pathway in a Selective Peroxisome Proliferator-Activated Receptor Alpha (PPAR-α)-Dependent Manner - Sarnelli, Giovanni; D’Alessandro, Alessandra; Iuvone, Teresa; Capoccia, Elena; Gigli, Stefano; Pesce, Marcella; Seguella, Luisa; Nobile, Nicola; Aprea, Giovanni; Maione, Francesco; de Palma, Giovanni Domenico; Cuomo, Rosario; et al. (PLOS ONE, 2016)
Background and Aim Angiogenesis is emerging as a pivotal process in chronic inflammatory pathologies, promoting immune infiltration and prompting carcinogenesis. Ulcerative Colitis (UC) and Crohn’s Disease (CD) represent paradigmatic examples of intestinal chronic inflammatory conditions in which the process of neovascularization correlates with the severity and progression of the diseases. Molecules able to target the angiogenesis have thus the potential to synergistically affect the disease course. Beyond its anti-inflammatory effect, palmitoylethanolamide (PEA) is able to reduce angiogenesis in several chronic inflammatory conditions, but no data about its anti-angiogenic activity in colitis have been produced, yet. Methods The effects of PEA on inflammation-associated angiogenesis in mice with dextran sulphate sodium (DSS)-induced colitis and in patients with UC were assessed. The release of Vascular Endothelial Growth Factor (VEGF), the hemoglobin tissue content, the expression of CD31 and of phosphatidylinositol 3-kinase/Akt/mammalian-target-of-rapamycin (mTOR) signaling axis were all evaluated in the presence of different concentrations of PEA and concomitant administration of PPAR-α and -γ antagonists. Results Our results demonstrated that PEA, in a selective peroxisome proliferator activated receptor (PPAR)-α dependent mechanism, inhibits colitis-associated angiogenesis, decreasing VEGF release and new vessels formation. Furthermore, we demonstrated that the mTOR/Akt axis regulates, at least partly, the angiogenic process in IBD and that PEA directly affects this pathway. Conclusions Our results suggest that PEA may improve inflammation-driven angiogenesis in colonic mucosa, thus reducing the mucosal damage and potentially affecting disease progression and the shift towards the carcinogenesis.